Effect of Mirror Therapy on Motor Function in Extremities and Daily Activities in Stroke Patients (Medico Legal Update, 2021)
Stroke is disease cause of partial loss some of brain functions that can lead to many of disorders, such asmotor, perception, language, sensory, and can lead to limitation in daily activities. Mirror therapy (MT) is anew therapeutic method used for stroke patients. This short review was intended to assess the effect of theMT on motor function in extremities and daily activities in stroke patients. The electronic searching wasconducted in Google Scholar and PubMed. this review paper confirmed that that apply of MT on strokepatients give benefits and significant improve the some of motor function and some of daily activities.Further studies are essential to verify MT long-term effects and its impact on daily activities among strokepatients.